The Influence of Light on the Human Body: A Case Study of Fluorescent Lights with a Color Temperature of 8500 Kelvin - Soenanta, Andy (Fakultas Teknik, Universitas Katolik Widya Mandala Surabaya, 2025)
Artificial lighting plays a significant role in modern human life, especially in structuring work environments to enhance productivity and comfort. To date, research and development in artificial lighting have focused on increasing energy efficiency (lumen per watt) and light quality (better color rendering). Another essential aspect of lighting is color temperature, which is often claimed to have various effects on human energy and performance. A noteworthy example is the high color temperature fluorescent lamps (8500 Kelvin) marketed by Osram, which were believed to boost employee energy in office settings. This article discusses the role of high color temperature lighting in the context of employee productivity and health, and it compares scientific evidence with marketing claims.